Association between physical activity and cognitive function in post-menopausal women with high parity: the chain-mediating effects of nutritional status and depression - Xiaotong Chen; Kai Wei; Shanshan Peng; Na Liu; Leqi He; Biying Wu; Meifang Shi; Yong Lin (BMC Women's Health)
Abstract Background It has been reported that the cognitive responses to physical activity (PA) in postmenopausal women vary by parity status, and women with higher parity show a significant association between PA and cognitive function. However, the potential pathways mediating the relationship between PA and cognitive function in women with higher parity remain unclear. The objective of this study was to examine this association in Chinese cohort and further investigate the mediating pathways. Methods A total of 2296 postmenopausal women were enrolled from the Baoshan District, from April to December 2020. All participant information was collected through interviewer-administered questionnaires or measurements, including personal information, medical history, lifestyle, body mass index (BMI), cognitive function, nutritional status, and depression status. In this cross-sectional study, generalized linear regression models and the chain-mediation analysis were used to examine the relationship between PA and cognitive function and the mediating pathways. Results There was a significant relationship between PA and cognitive function in the high-parity group (≥ three births). In the fully adjusted generalized linear regression model, PA was significantly associated with cognitive function [β: 0.795, 95% confidence interval (CI): 0.251–1.340, P < 0.05]. The chain-mediation analysis showed that depression and nutritional status were two significant mediators, contributing 37.96% of the indirect effect of the overall effect. Conclusions Our findings suggest that PA is beneficial for women (≥ three births) to maintain cognitive function, and these benefits are mediated by depression and nutritional status.